How the Learning Environment Influences Bullying: The Case of Two Universities in Ghana - Emmanuel Mensah Kormla Tay; Stephen Zamore (African Journal of Teacher Education, 2022)
Organisational climates determine the experiences, well-being, and output of people. In response to a growing concern about bullying and victimisation at universities, this study examined students’ perception of the university learning environment concerning their experience of various negative behaviours and victimisation at two public universities in Ghana. The study is a cross-sectional survey of 751 respondents. Confirmatory Factor Analysis (CFA) and regression analysis indicate how perceptions of the universities’ learning environment are related to students’ experiences. With an inverse relationship between students’ perception of the learning environment and their experience of various negative behaviours and victimisation, the study suggests that awareness of anti-bullying rules, which are strictly, fairly, and consistently enforced through participatory democratic principles, will be essential to ensure a positive psychosocial learning environment.